Design And Evaluation Of A Dual Core Erbium Doped Fiber Amplifier (Dc-Edfa) - Alsharjabi, Abdullatif Mohammed (2003)

(untitled)
Traditional erbium doped fiber amplifiers EDFA (unidirectional signaling) can only amplify signals propagating in a single direction, as some isolators must be installed to eliminate the reflections from end faces and fusion points. This means the amplifiers only amplify signal in one direction over a fiber. For long haul transmission, many amplifiers are placed along each single mode fiber. Total numbers of the amplifiers will be the number of the amplifier over a fiber multiply by the number of the fibers in the cable. This means a large number of amplifiers are required thus increasing a high cost. In order to reduce the system cost, and increase the capacity, many studies have been done using bi-directional signaling in a single fiber (duplex), through one or two separate amplifiers. In this work, a bi-directional signaling technique has been exploited, this in order to amplify the signals bi-directionally, over two single mode fibers (unidirectional) . This is achieved by using two circulators instead of isolators at the terminals of the EDFA. The main goal is to reduce the number of amplifiers in the optical communication system, which results in a decrease in the system cost. The new system is tested by laboratory experiments. From the results, it is found that the system has the same characterizations as bi-directional EDFA amplifiers, (i.e. independent amplification, medium gain, low ASE), as expected. Reflections also occur. The system has high reflection when the difference in the input powers of the bidirectional signals is high. This causes different gains and different amplified powers. The reflection of the signal which has higher input power is associated with the other main signal (over the other fiber). The system shows the best performance, when the difference in the input powers (for the two fibers) is small and is even better when the bidirectional signals have the same input powers. In conclusion, the project objectives have been achieved, and the system can reduce the number of the amplifiers to as much as 50% of that in a unidirectional propagating system, due to the fact that, two fibers can now share one amplifier and results in cost reduction by almost 50%. Furthermore, the approach is flexible and simple.